Efficient synthesis of alkyl levulinates fuel additives using sulfonic acid functionalized polystyrene coated coal fly ash catalyst - Yi Tian; Xiaoting Zhu; Shuolin Zhou; Wenguang Zhao; Qiong Xu; Xianxiang Liu (Journal of Bioresources and Bioproducts, 2023)
In this study, sulfonic acid functionalized polystyrene coated coal fly ash catalyst (CFA@PS-SO3H) was designed and prepared by the post-synthesis method, which exhibited excellent catalytic performance for esterification of levulinic acid (LA) to afford alkyl levulinates. Four significant factors, including reaction time, catalyst dosage, alcohol-to-acid molar ratio and reaction temperature were evaluated systematically. Response surface methodology based on Box-Behnken design (BBD) was carried out to determine the optimal parameters. The maximum yield could reach 99.6% under the mild conditions. Furthermore, kinetics of the esterification reaction between levulinic acid and n-butanol were analyzed and the activation energies of the first and second step of esterification reaction were found to 52.18 and 59.81 kJ/mol, respectively. The CFA@PS-SO3H also showed high catalytic activity for the esterification of levulinic acid with other linear alcohols, which made it a low cost, environmentally friendly and promising solid catalyst for the synthesis of alkyl levulinates.